Isolation and Bioactivity Screening of Endophytic Fungi from Commelina diffusa - Nasrin, Mahmuda; Afroz, Farhana; Begum, Mst. Nadira; Rony, Satyajit Roy; Sharmin, Suriya; Moni, Fatema; Rana, Md. Sohel; Sohrab, Md. Hossain (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Endophytic fungi are able to produce many secondary metabolites and thus their availability and biological activity created new horizons for different pharmaceutical and agricultural approaches. Objective: For the ethnobotanical antiquity of Commelina diffusa in Bangladesh, this study is aimed at evaluating the endophytic fungal collection of Commelina diffusa and their bioactive potential. Methods: Endophytic fungi were isolated by the surface sterilization technique and identified using the microscopic procedure. Isolated fungal strains were solvent extracted. Disc diffusion method, DPPH free radical scavenging assay, brine shrimp lethality bioassay had been used for the determination of antibacterial, antioxidant, cytotoxic activities respectively. Results: Eight fungal strains were isolated and six of them were identified up to the genus level as Fusarium sp. (CDLE 1, CDRE 1, CDRE 2, CDRE 3, CDBE 1) and Alternaria sp. (CDBE 3) according to morphological and microscopical characters. Three of the eight isolated endophytes i.e., CDBE 2, CDRE 1 and CDRE 2 showed potential activity against A. niger in comparison with ketoconazole (30 µg/disc). Ethyl acetate extract CDBE 3 fungal extract demonstrated significant antioxidant and cytotoxic activities. Conclusion: The present study has proven that Commelina diffusa may be a rich source of medicinally important endophytic fungi and our findings may form a basis for further studies on endophytic fungi from medicinal plants for use in medicine, industry and agriculture.
Keywords: Endophytic fungi; Fusarium sp.; Alternaria sp.; Antibacterial; Antioxidant; Cytotoxic activity